Maternal outcomes in patients with previous one lower segment caesarean section undergoing trial of labour: prospective observational study - ., Veeramma; Mahajan, Puneeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The incidence of caesarean section is on the rise and has increased 2-3 folds from the initial rate of 10% during the last decade. The objective of the present study was to compare maternal outcomes in successful and failed trial of labour in women with previous one LSCS. Methods: This prospective observational study was carried out in Department of obstetrics & Gynaecology, Sanjay Gandhi memorial Hospital, New Delhi during 2015-2016 and included 150 gravid women with previous LSCS. The study was undertaken during March 2015 to May 2016. The ethical committee approval for the study has been taken. Results: out of 150 patients who had given a trial of labour, 64.7% (97) underwent successful VBAC and 35.3 %( 53) underwent emergency repeat LSCS. Majority of cases 59.3% were in age group <25 years followed by 36.7% in age group of 25-30 years. Most of the cases are para one 72.7% and remaining are multipara (27.3%). LSCS group: 83% para1 and 17% are multipara. VBAC group: 67.01 % para 1 and 32.9% multipara. There is no significant statistical difference between parity and mode of delivery. (p=0.591). Majority of cases 52.7% were in between 37-39 weeks and 47.3% cases were in between 39-42 weeks. Majority cases 89.3% had Bishop’s score 4-6 and 10.7% had Bishops score >6. Conclusions: This study reveals that successful VBAC rate was 64.7% and 35.3% emergency repeat caesarean section.